USE OF BELKALIGAM MEDIA TO IMPROVE UNDERSTANDING OF THE CONCEPT OF MULTIPLICATION IN CLASS II SDN 2 BAMBEL ACEH TENGGARA - Kemiten, Tiara; Safiah, Intan; Fauzi, Fauzi (Elementary Education Research, 2023)
This research aims to describe student activities, teacher activities and to determine student learning outcomes through the use of belkaligam media in multiplication calculation operations in class II at SDN 2 Bambel, Southeast Aceh. The subjects in this research were 19 students, consisting of 11 women and 8 men. The data collection techniques used are observation and tests. Data analysis uses qualitative descriptive analysis using the percentage formula. The results of the data analysis carried out showed that there was an increase in teacher activity in managing learning in cycle I, getting an average score of 2.9 with good criteria, cycle II got an average score of 3.4 with very good criteria. Student activity in learning showed an increase in cycle I with an average score of 44.75 with sufficient criteria, in cycle II the average score was 82.44 with very good criteria. Student learning outcomes show an increase, this is shown by the average value of the first cycle test results of 67.89, the second cycle of 84.21, this increase has reached the complete indicator. From the results of data analysis, it was concluded that the use of belkaligam media to increase understanding of the concept of multiplication can improve the learning outcomes of class II students at SDN 2 Bambel, Southeast Aceh.